Focusing Effect in Multimode Vertical Cavity Surface Emitting Lasers by Parallel Trenches Surface Profiling - TEE, Chyng Wen (Institutional Knowledge at Singapore Management University, 2005)
Surface profiling of parallel trenches is shown to be capable of introducing a transverse waveguiding effect to the optical modes of a gain-guided VCSEL, resulting in a dramatic reduction of emission spot-size and spatial filamentation.